2023
DOI: 10.48550/arxiv.2303.02857
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Weakly Supervised Realtime Dynamic Background Subtraction

Abstract: Background subtraction is a fundamental task in computer vision with numerous real-world applications, ranging from object tracking to video surveillance. However, dynamic backgrounds can pose a significant challenge in this problem. While various methods have been proposed for background subtraction, supervised deep learning-based techniques are currently considered state-of-the-art. However, these methods require pixelwise ground-truth labeling, which can be time-consuming and expensive. In this work, we pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In other words, we investigated the merging of components of two datasets involving humans as an additional augmentation technique. In the realm of background removal, an emerging trend is to incorporate deep learning-based approaches [28][29][30] to accomplish the background removal task. A comparison study in [29] revealed the practicability of YOLO models [20] in comparison to other feature engineering-based approaches [31,32] in removing distinct moving particles from their liquid background contexts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, we investigated the merging of components of two datasets involving humans as an additional augmentation technique. In the realm of background removal, an emerging trend is to incorporate deep learning-based approaches [28][29][30] to accomplish the background removal task. A comparison study in [29] revealed the practicability of YOLO models [20] in comparison to other feature engineering-based approaches [31,32] in removing distinct moving particles from their liquid background contexts.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison study in [29] revealed the practicability of YOLO models [20] in comparison to other feature engineering-based approaches [31,32] in removing distinct moving particles from their liquid background contexts. The proposed method in [28] incorporates an autoencoder along with a U-Net [33] to accomplish static and dynamic background generation tasks, respectively. Here, a set of static backgrounds were used to train an autoencoder.…”
Section: Introductionmentioning
confidence: 99%